2005
DOI: 10.1152/ajpgi.00138.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p-ERK1/2 by nicotine in pancreatic tumor cell line AR42J: effects on proliferation and secretion

Abstract: The objectives of the present study were to determine the effect of nicotine on MAPK signaling and on the proliferation of AR42J cells as well as to assess the relationship between MAPK activation and exocrine secretion in these cells. AR42J cells were incubated with nicotine and analyzed for the activation of MAPK by Western blot analysis using their respective antibodies and confirmed by immunohistochemistry. The effect of nicotine on cell proliferation was determined by the spectrophotometric method, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 60 publications
6
43
0
Order By: Relevance
“…Nicotine exerts its biological effects by binding to the nAChRs, thus leading to the activation of a cascade of signaling pathways (44), which include the influx of Ca 2+ and activation of calmodulin, PKC (40,45), c-Src, Janus-activated kinase 2/signal transducers and activators of transcription 3 (11, 38 -40), PI3K/Akt/mammalian target of rapamycin (5,35,46), and Raf-1/mitogen-activated protein kinase/ERK1/2 (7,34,45). In the present study, we also showed that nicotine activates both PI3K/Akt and ERK1/2 signaling pathways (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine exerts its biological effects by binding to the nAChRs, thus leading to the activation of a cascade of signaling pathways (44), which include the influx of Ca 2+ and activation of calmodulin, PKC (40,45), c-Src, Janus-activated kinase 2/signal transducers and activators of transcription 3 (11, 38 -40), PI3K/Akt/mammalian target of rapamycin (5,35,46), and Raf-1/mitogen-activated protein kinase/ERK1/2 (7,34,45). In the present study, we also showed that nicotine activates both PI3K/Akt and ERK1/2 signaling pathways (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In dispersed pancreatic acini, the same group showed that CCK-8 and TNF-␣ initiate NF B activation by different PLC pathways that converge at the level of the protein kinase Cs (PKC-␦ and -) to mediate NF B activation [42] . A study investigating the effect of nicotine on AR42J cells showed that it activates ERK but not p38 or JNK [43] . Lysophosphatidylcholine, a phospholipid by-product generated by phospholipase A2, activated stress kinases (ERK, JNK, and p38) and increased the specific DNA-binding activity of NF B and AP-1 [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, one of the main chemicals in tobacco, is known to be the primary psychoactive ingredient that has been responsible for reinforced behavior in smokers. Previous studies have shown that nicotine exposure has been associated with a variety of organ damages [3], including its effects of on pancreatic acinar cells [4][5][6][7]. An exploratory study on the development of an animal model of acute pancreatitis following exposure to nicotine has been reported [8].…”
Section: Introductionmentioning
confidence: 99%